SCN2A-Related Epilepsy: The Phenotypic Spectrum, Treatment and Prognosis - Zeng, Qi; Yang, Ying; Duan, Jing; Niu, Xueyang; Chen, Yi; Wang, Dan; Zhang, Jing; Chen, Jiaoyang; Yang, Xiaoling; Li, Jinliang; Yang, Zhixian; Jiang, Yuwu; et al. (Frontiers in Molecular Neuroscience, 2022)
Objective The aim of this study was to analyze the phenotypic spectrum, treatment, and prognosis of 72 Chinese children with SCN2A variants. Methods The SCN2A variants were detected by next-generation sequencing. All patients were followed up at a pediatric neurology clinic in our hospital or by telephone. Results In 72 patients with SCN2A variants, the seizure onset age ranged from the first day of life to 2 years and 6 months. The epilepsy phenotypes included febrile seizures (plus) (n = 2), benign (familial) infantile epilepsy (n = 9), benign familial neonatal-infantile epilepsy (n = 3), benign neonatal epilepsy (n = 1), West syndrome (n = 16), Ohtahara syndrome (n = 15), epilepsy of infancy with migrating focal seizures (n = 2), Dravet syndrome (n = 1), early infantile epileptic encephalopathy (n = 15), and unclassifiable developmental and epileptic encephalopathy (n = 8). Approximately 79.2% (57/72) patients had varying degrees of developmental delay. All patients had abnormal MRI findings with developmental delay. 91.7% (55/60) patients with de novo SCN2A variants had development delay, while only 16.7% (2/12) patients with inherited SCN2A variants had abnormal development. 83.9% (26/31) SCN2A variants that were located in transmembrane regions of the protein were detected in patients with development delay. Approximately 69.2% (9/13) SCN2A variants detected in patients with normal development were located in the non-transmembrane regions. Approximately 54.2% (39/72) patients were seizure-free at a median age of 8 months. Oxcarbazepine has been used by 38 patients, and seizure-free was observed in 11 of them (11/38, 28.9%), while 6 patients had seizure worsening by oxcarbazepine. All 3 patients used oxcarbazepine and with seizure onset age > 1 year presented seizure exacerbation after taking oxcarbazepine. Valproate has been used by 53 patients, seizure-free was observed in 22.6% (12/53) of them. Conclusion The phenotypic spectrum of SCN2A-related epilepsy was broad, ranging from benign epilepsy in neonate and infancy to severe epileptic encephalopathy. Oxcarbazepine and valproate were the most effective drugs in epilepsy patients with SCN2A variants. Sodium channel blockers often worsen seizures in patients with seizure onset beyond 1 year of age. Abnormal brain MRI findings and de novo variations were often related to poor prognosis. Most SCN2A variants located in transmembrane regions were related to patients with developmental delay.